2020
DOI: 10.3892/ol.2020.11613
|View full text |Cite
|
Sign up to set email alerts
|

High levels of global genome methylation in patients with retinoblastoma

Abstract: Retinoblastoma is a tumor of the embryonic neural retina in young children. The DNA methyltransferase 1 (DNMT1) gene has been demonstrated to be transcriptionally activated in cells lacking retinoblastoma 1 (RB1). Thus, there is a direct interaction between DNMT1 and RB1 in vivo. The present study hypothesized that uncontrolled DNMT1, DNMT2 and DNMT3 expression may lead to a high level of global genome methylation causing a second hit or where both alleles are altered, in RB1 and/or inactivation of other genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Future studies may expand upon these results by considering more downstream analytes, such as DNA methylation or RNA expression, to assess biological differences between patients either dependent or independent of DNA mutations. For example, recent studies have considered genome-wide methylation and found expression patterns unique to retinoblastoma, suggesting their importance to oncogenesis [ 40 , 41 ]. Further clinical assessment of patient phenotypes alongside various biological measurements may yield important insight into the progression of retinoblastoma from DNA mutation to unique clinicopathological features of retinoblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may expand upon these results by considering more downstream analytes, such as DNA methylation or RNA expression, to assess biological differences between patients either dependent or independent of DNA mutations. For example, recent studies have considered genome-wide methylation and found expression patterns unique to retinoblastoma, suggesting their importance to oncogenesis [ 40 , 41 ]. Further clinical assessment of patient phenotypes alongside various biological measurements may yield important insight into the progression of retinoblastoma from DNA mutation to unique clinicopathological features of retinoblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…In normal cells of the human body, the level of MGMT expression depends on their type, it is not stable and varies in different individuals. Regulation of MGMT gene expression is carried out by various intracellular systems, including and p53 protein-mediated [10]. Especially low expression of reparative enzyme in brain tissues [11].…”
Section: Research Resultsmentioning
confidence: 99%
“…However, it is possible that HDACi, through enhanced P21 gene and p21 protein expression, also enhanced pRb dephosphorylation that blocks the cell cycle, as shown previously [ 44 ]. Inactivation of the retinoblastoma gene has recently been associated with high levels of global DNA methylation [ 45 ], while histone acetylation by an HDACi could induce DNA demethylation [ 46 ]. However, we did not assess any global DNA-methylation changes in VPA-treated embryos compared to controls.…”
Section: Discussionmentioning
confidence: 99%